Kesalahan Umum dalam Pola Asuh Anak dan Dampaknya terhadap Perkembangan - Putri, Aurel Salbila (TSAQOFAH, 2026)
Parenting mistakes often occur without parents’ awareness, for instance in the form of inconsistency, overindulgence, and insufficient emotional validation, all of which can lead to long-term psychological and social problems in children. This study aimed to comprehensively examine various forms of common parenting errors, identify their causal factors, analyze the negative impacts on children’s physical, emotional, social, and moral development, and formulate practical strategies and solutions for more effective and positive parenting practices. The method employed was a literature review with a descriptive-analytical approach based on written reports from the service area of Puskesmas Ulee Kareng and data from BPS (2024), combined with an examination of theories of child development and parenting. The findings show that inappropriate parenting errors have significant consequences, including decreased self-confidence, increased anxiety, difficulties in socializing, and a lack of independence in children, thereby underscoring the importance of responsive and consistent parenting. The study concludes that parenting education and the implementation of positive parenting strategies that emphasize open communication, empathy, and consistency are crucial to supporting children’s optimal growth and development and minimizing the negative impacts of parenting errors in the future.